Physicochemical Properties of Malaysian Fish Balls - Huda, Nurul; Abdullah, Aminah; A.S., Babji (Fishery Technology, 2025)
A total of 10 brands of Malaysian fish balls were analyzed for physiochemical properties like colour, cooking effect, proximate composition and texture (folding test). Results showed that there was a wide variation in the amount and types of ingredients used in producing the different kinds of fish balls. The weight of samples analyzed ranged between 6.25 - 15.14 g with price varying from US $ 1.97-3.62/kg. The colour value for lightness (L) of fish ball varied significantly (p